2022
DOI: 10.3389/fnhum.2021.788036
|View full text |Cite
|
Sign up to set email alerts
|

Neural Suppression Elicited During Motor Imagery Following the Observation of Biological Motion From Point-Light Walker Stimuli

Abstract: Introduction: Advantageous effects of biological motion (BM) detection, a low-perceptual mechanism that allows the rapid recognition and understanding of spatiotemporal characteristics of movement via salient kinematics information, can be amplified when combined with motor imagery (MI), i.e., the mental simulation of motor acts. According to Jeannerod’s neurostimulation theory, asynchronous firing and reduction of mu and beta rhythm oscillations, referred to as suppression over the sensorimotor area, are sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
(134 reference statements)
0
3
0
Order By: Relevance
“…Previous investigations on limb motor imagery have reported that short-term motor imagery could induce the ERD pattern in the contralateral brain cortex and ERS in the ipsilateral brain cortex, while long-term (5 s) motor imagery caused the ERS pattern [ 57 , 58 ]. Grazia et al have reported that subjects performing 10 s of motor imagery of walking and bicycling after observing the movements showed an ERS pattern in the sensorimotor cortex, which was attributed to the fact that walking and cycling were closer to an automatic movement [ 33 ]. In this research, Figure 2 showed the spatial distribution of ERS/ERD of the whole brain: it showed that ERS predominated in nearly the whole brain in the alpha and beta bands in M-AIG, F-AIG, and CG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations on limb motor imagery have reported that short-term motor imagery could induce the ERD pattern in the contralateral brain cortex and ERS in the ipsilateral brain cortex, while long-term (5 s) motor imagery caused the ERS pattern [ 57 , 58 ]. Grazia et al have reported that subjects performing 10 s of motor imagery of walking and bicycling after observing the movements showed an ERS pattern in the sensorimotor cortex, which was attributed to the fact that walking and cycling were closer to an automatic movement [ 33 ]. In this research, Figure 2 showed the spatial distribution of ERS/ERD of the whole brain: it showed that ERS predominated in nearly the whole brain in the alpha and beta bands in M-AIG, F-AIG, and CG.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the band specificity of ERSPs, it was easily observed only at ~10 Hz and ~20 Hz [ 31 ], and in other frequency bands (e.g., delta, theta, and gamma), it tended to show only ERS patterns [ 32 ]. In addition, most studies of motor imagery focused on the alpha and beta bands [ 21 , 33 ]. Therefore, in the present study we only analyzed the alpha and beta bands.…”
Section: Methodsmentioning
confidence: 99%
“…Motor imagery (MI) EEG signals generated in the motor cortex are one of the most widely studied BCI paradigms [8]. The power of alpha (8)(9)(10)(11)(12)(13) and beta (14-30 Hz) rhythms is inhibited or promoted in the sensorimotor cortex of the brain and the amplitude of the EEG signal decreases or increases, accompanied by the phenomenon of spectral oscillation when the user imagines or performs an action with their hands, feet, or tongue [9]. MI mainly induce event-related desynchronization (ERD)/Event-related synchronization (ERS) in the alpha and beta bands.…”
Section: Introductionmentioning
confidence: 99%
“…We will specifically look for differences in event-related desynchronization (ERD), which is said to reflect an activation of the brain area concerned and event-related synchronization (ERS), or deactivation of concerned brain areas, as introduced by Pfurtscheller and Da Silva ( 1999 ). ERD/S values are commonly used in recent studies (Wriessnegger et al, 2018 ; Zapała et al, 2021 ; Grazia et al, 2022 ) and are popular as features in MI-based BCI systems (Pfurtscheller and Neuper, 2006 ; Hwang et al, 2013 ; Wierzgała et al, 2018 ; Singh et al, 2021 ). Here, ME is used as a control condition as it is already well known that MI brain activity parallels that of ME (Kraeutner et al, 2014 ), and the underlying neural correlates are quite clear (Pfurtscheller, 2000 ; Neuper et al, 2006 ; Nakayashiki et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%